(untitled) (Eureka Journal of Physical and Chemical Research, 2025)
Diabetes is one of the intensively developing diseases, and chronic hyperglycemia causes protein glycosylation, glucose autoxidation, and a sharp increase in the active forms of oxygen. Chronic hyperglycemia causes high oxidative stress. As a result, the amount of free radicals increases. This causes damage to the heart, kidney, blood vessels and nervous system of vital organs [15].